2008
DOI: 10.1080/03079450802043734
|View full text |Cite
|
Sign up to set email alerts
|

The VG/GA strain of Newcastle disease virus: mucosal immunity, protection against lethal challenge and molecular analysis

Abstract: The VillegasÁGlisson/University of Georgia (VG/GA) strain of Newcastle disease virus (NDV) isolated from the intestine of healthy turkeys has been proposed to replicate in the respiratory and intestinal tract of chickens. In the present study, the virus distribution, the mucosal and systemic immune response, the efficacy against lethal challenge and the full genome sequence of the VG/GA strain were compared with the La Sota strain of NDV. The VG/GA strain was detected at different time points in the respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
26
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 35 publications
8
26
0
2
Order By: Relevance
“…The level of protection offered by La Sota vaccine in SPF and commercial hens in the present study concurs with findings from previous studies although no effort was made to compare La Sota with other lentogenic vaccines in this study (Parede and Young, 1990;Beard et al, 1993;Kapczynski and King, 2005;Miller et al, 2007;Perozo et al, 2008). A single application of La Sota ND vaccine conferred protection against clinical ND in the present study since none of the immunologically naïve SPF birds manifested clinical signs or died after challenge (Rehmani, 1996).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The level of protection offered by La Sota vaccine in SPF and commercial hens in the present study concurs with findings from previous studies although no effort was made to compare La Sota with other lentogenic vaccines in this study (Parede and Young, 1990;Beard et al, 1993;Kapczynski and King, 2005;Miller et al, 2007;Perozo et al, 2008). A single application of La Sota ND vaccine conferred protection against clinical ND in the present study since none of the immunologically naïve SPF birds manifested clinical signs or died after challenge (Rehmani, 1996).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, earlier works indicated that NDV antigen cannot be detected earlier than 3 days PV (Rao et al, 2002;Perozo et al, 2008), viral antigen was evidently demonstrated on day 2 PV in commercial birds (probably this was associated with prior NDV vaccination) and on day 4 PV in SPF birds (Table 2a).…”
Section: Discussionmentioning
confidence: 87%
“…Regardless of the genotype differences between NDV strains circulating worldwide, all NDV isolates belong to the same serotype; if given correctly, ND vaccines prepared with any NDV should protect poultry from clinical disease and mortality in the event of a virulent challenge (21,23,27). Current vaccination strategies do protect against mortality; however, existing vaccines have proven to be incapable of completely stopping viral excretion after infection, leading to high recirculation of the virus in the environment and to a viral population suitable to mutations and adaptive changes (17,18).…”
Section: Resultsmentioning
confidence: 99%
“…NDV vaccine strains of genotypes I and II are used to control detrimental effects of subclinical forms of the disease and severe clinical disease during outbreaks (2,23,27). Additionally, control of risk factors, including immunosuppressive agents, biosecurity breaks, inadequate management practices, and harsh environments, together with common sense, is required to diminish the economic impact of this and other poultry diseases (5).…”
mentioning
confidence: 99%
“…The VG/GA strain preferentially replicates in the intestinal tract of chickens and induces local mucosal immunoresponses (Perozo et al, 2008a). Vaccination of chickens with the VG/GA vaccine provided 100 % protection of mortality to chickens against a velogenic viscerotropic NDV challenge (Beard et al, 1993;Perozo et al, 2008b). Therefore, the VG/GA strain is considered as a potential enterotropic vaccine vector to deliver antigens of poultry enteric viruses as bivalent vaccines.…”
mentioning
confidence: 99%